Development of spherical isotropic power reactor design for enhancement of safety and economics in power production. (27th October 2011) - Woo, T.H.; Noh, S.W.; Cho, H.S.; Kim, T.W.; Kim, Y.I.
Following the civilian design development trend of Nuclear Power Plants (NPPs), a newly introduced NPP has been investigated. The conceptual study for isotropic power production is done by the water-cooled reactor. A new design of core geometry can improve the safety and economics of power production. The newly designed Spherical Isotropic Power Reactor (SIPR) has been analysed. The configuration of nuclear fuel for SIPR is suggested. Hence, a new design could give improved results in the economics as well as the safety aspects. The molecular nanoscopic reactions are focused on a significant improvement in power production. One possible accident scenario is given. This paper gives the basic concept in the proposed development of the plant construction, which will be done within next decade.